Strategi Pemasaran Produk Simpanan Dalam Meningkatkan Jumlah Nasabah Pada BMT Mitra Muamalat Kudus - Fera Wahyuningsih; Ishlahud Dimam; Kharis Fadlullah Hana (Institut Agama Islam Negeri Madura, 2022)
Abstract: This study was carried out with the aim of describing and analyzing the marketing strategy of savings products at the Baitul Maal Wat Tamwil (BMT) financial institution Mitra Muamalat, Kudus City. The research method used is a type of qualitative research with data collection techniques through direct observation and interviews with several informants, namely managers, branch coordinators, account officers, and customers at BMT Mitra Muamalat Kudus. The results of this study indicate that each marketing strategy has its own advantages depending on the intended target market. The marketing strategy at BMT Mitra Muamalat Kudus which is considered effective in increasing the number of customers is